Outsourcing: Analisis Ketidakpastian Hubungan Kerja Yang Mengarah Pada Modern Slavery Perspektif Teori Keadilan John Rawls (International Forum of Researchers and Lecturers, 2023)
Outsourcing means handing over part of the work implementation to another company through a work contract agreement or worker/labor service provider. This research aims to analyze the form of disharmony in legal norms in outsourcing policies in Indonesia, and to analyze the protection of outsourced workers in terms of John Rawls's theory of Justice. This research is normative research using primary and secondary data obtained from literature reviews and statutory regulations related to the issues raised. The results of this research show that the work relationship that is practiced in the outsourcing system based on Article 65 paragraph (8) of Law Number 13 of 2003 states that work relations that initially occur between workers/laborers and the company receiving the work can in certain cases change to work relations between workers/laborers. with the employing company. This shift creates problems because from the start, employment relations only existed between the employer company and the workers/laborers. After the decision of the Constitutional Court Number 27/PUU-IX/2011, the working relationship between outsourced workers/laborers and outsourcing companies can be carried out through a Specific Time Work Agreement (PKWTT) or a Certain Time Work Agreement (PKWT), but the implication of the Constitutional Court's decision is that if the employment relationship between workers/workers and outsourcing companies that are not based on PKWTT or PKWT, this will create uncertainty about the employment relationship status for outsourced workers/laborers. Regarding the protection of the uncertainty of employment relations between outsourced workers/laborers, John Rawls stated that it would be unfair to sacrifice the rights of one or several people just for the sake of greater economic benefits for society as a whole. Justice as fairness means that not only those who are talented and have better abilities -in this case permanent employees of a company have the right to enjoy various social benefits more, but these benefits must also open up opportunities for those who are less fortunate in terms of These are outsourced workers/laborers in order to improve their standard of living.